Moderate surface acetylation of nanofibrillated cellulose for the improvement of paper strength and barrier properties. Issue 74 (13th August 2015) - Mashkour, Mozhdeh; Afra, Elyas; Resalati, Hossein; Mashkour, Mahdi
<x xml:space="preserve">Abstract</x> This study evaluated the effect of using acetylated nanofibrillated cellulose (ANFC) and acetylated pulp (AP) fibers to modify strength and barrier properties of paper.